Healing homosexuality - Payne, Leanne (Michigan : Hamewith Books, 1996)
Originally published : The healing of the homosexual. Westchester, III. : Crossway Books (1985) .
Includes bibliography references
Keywords: Homosexuality -- Religious aspects -- Christianity